2017
DOI: 10.4314/sajas.v47i3.6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of polyethylene glycol inclusion in <i>Vachellia tortilis</i> leaf meal on nitrogen balance in growing pigs

Abstract: The incorporation of polyethylene glycol (PEG), a tannin binding agent, in high tannin feedstuff is known to prevent tannin-protein complexes. Environmental contamination with nitrogen-containing products in manure is a topical issue in the tropics. The objective of the study was to determine the extent to which the incorporation of PEG in Vachellia tortilis leaf meal improved nitrogen balance, serum iron, and phosphorus in growing pigs. Forty-eight clinically healthy male PIC pigs (31.3 ± 1.28 kg; Landrace x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Indeed, Besharati and Taghizadeh [13] reported that PEG breaks already formed tannin–protein complexes, due to its high tannin affinity. This was also confirmed by Hlatini et al [14] when PEG was included in Acacia tortilis leaf meal diets for pigs. While the use of PEG to inactivate condensed tannins in ruminant diets has been widely investigated, there are no documented studies on its application to improve GP utilization in broiler chickens.…”
Section: Introductionsupporting
confidence: 76%
“…Indeed, Besharati and Taghizadeh [13] reported that PEG breaks already formed tannin–protein complexes, due to its high tannin affinity. This was also confirmed by Hlatini et al [14] when PEG was included in Acacia tortilis leaf meal diets for pigs. While the use of PEG to inactivate condensed tannins in ruminant diets has been widely investigated, there are no documented studies on its application to improve GP utilization in broiler chickens.…”
Section: Introductionsupporting
confidence: 76%
“…The NR value was slightly higher in the LEW group, and was positively correlated with BVFT and NPU. The current results are close to those obtained in [21] using Vachellia tortilis leaf meal, although the percent of nitrogen retained was higher in our research (>46% compared to 42%), probably due to the lower fecal nitrogen output in our case. In a previous study [22], two levels of protein and inulin in the diet were used, and a similar fecal nitrogen level was found, while the urinary nitrogen resulted as higher than the level obtained in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Environmental contamination with nitrogen-containing products in manure is a topical issue in the tropics. Hlatini et al (2017) reported that increasing levels of PEG resulted to an increase in serum iron concentration until it reached a plateau then it started to decrease. The Authors also observed a linear increase in nitrogen utilisation and retention with PEG inclusion.…”
Section: Performance Of Pigs Fed Leguminous Leaf Meal Treated With Polyethylene Glycolmentioning
confidence: 99%